Synthesis and characterization of organotin (IV) complexes derived of 3-(dimethylamino)benzoic acid: In vitro antibacterial screening activity - Win, Yip Foo; Teoh, Siang Guan; Vikneswaran, Murugaiyah; Sivasothy, Yasodha; Ha, Sie Tiong; Ibrahim, Pazilah (American-Eurasian Network for Scientific Information, Jordan, 2010)
Organotin(IV) carboxylate complexes derivative of 3-(dimethylamino)benzoic acid, 3-[N(CH3)2]C6H4COOH have been successfully synthesized. Two types of diorganotin(IV) complexes, [{3-[N(CH3)2]C6H4COO(R)2Sn}2O]2 dimer (R= methyl 1, butyl 3) and {3-[N(CH3)2]C6H4COO}2 (C4H9)2Sn, 2 (monomer) as well as 3-[N(CH3)2]C6H4COO(C6H5)3Sn, 4 were successfully synthesized and obtained in solid state. The acid and complexes 1 - 4 obtained were characterized quantitatively using C, H, N and Sn elemental analysis as well as spectroscopic methods such as infrared (FTIR) and nuclear magnetic resonance (1H, 13C, 1H-13C HMQC & 119Sn NMR). Infrared spectroscopy showed that the coordination took place via oxygen atoms from the carboxylate anions. From 13C NMR spectroscopy data, the δ(COO) of complexes 1-4 are shifted to lower field compared to the parent acid indicated the coordination of carboxylate anion to the tin atom moiety. Moreover, the complexes obtained were screened for their in vitro antibacterial activity. Complex 4 was found to be most active against Bacillus subtilis and Staphylococcus aureus bacterial strains compared to complexes 1-3. © 2010, INSInet Publication.